EFFECT OF ACUTE AND SUB-LETHAL CONCENTRATION OF THE PHYTOTOXIC PLANT, Thevetia neriifolia LEAVES ON THE GROWTH, SURVIVAL AND BLOOD PROFILES OF JUVENILES Clarias gariepinus: Effects of Thevetia neriifolia Leaves on Clarias gariepinus - OLUSOLA, Sunday Emmanuel; ABULU, Oisereme Eghoise; AYEBIDUN, Omotola Victoria; AGBEBI, Funmilola Omolara (Polish Journal of Natural Sciences, 2023)
This study investigated the effects of acute and sub-lethal concentrations of Thevetia neriifolia leaves on growth, survival and blood profiles of Clarias gariepinus juveniles. Twenty (20) Clarias gariepinus (mean weight 15.65±0.00g) were exposed to T. neriifolia leaves extract at 0.00, 0.04, 0.08, 0.15, 0.30 and 0.60 ml/L concentrations respectively for 28 days and 14 days’ withdrawal and replicated twice. The result revealed a general increase in weights among the treatments, but the values decreased as the concentration of T. neriifolia increased. The haematological and plasma biochemistry indices show variables relative to the exposure concentration. No observable lesions were observed in the control group while there was moderate diffuse atrophy of hepatocytes in gills, liver and the skin of the exposed groups The result of this study indicates that the exposure to sub-lethal levels of T. neriifolia leaves impacted the growth parameters, histology and blood profiles of the exposed fish.